2022
DOI: 10.3390/jcm11092648
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-Term Outcomes after Propofol-and Sevoflurane-Based Anesthesia in Colorectal Cancer Surgery: A Retrospective Study

Abstract: Background: Propofol is considered to protect against immunosuppression and has lower inflammatory responses in the perioperative period than volatile agents. We evaluated whether the anesthetic agent is associated with cancer outcomes. Methods: We retrospectively reviewed 2616 patients who underwent colorectal cancer surgery under general anesthesia between 2016 and 2018 (follow-up closure: July 2021) at a single institution. Patients received propofol-based total intravenous anesthesia or sevoflurane-based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…After identifying 4315 references, 1035 duplicate publications and 3205 irrelevant studies were excluded, leaving 75 potentially eligible studies ( Figure 1 ). Finally, six cohort ( 17 , 18 , 21 24 ) studies conducted between 2014 and 2022 were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After identifying 4315 references, 1035 duplicate publications and 3205 irrelevant studies were excluded, leaving 75 potentially eligible studies ( Figure 1 ). Finally, six cohort ( 17 , 18 , 21 24 ) studies conducted between 2014 and 2022 were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective analysis showed that volatile anaesthetics slightly increased the cancer recurrence rate in patients undergoing colorectal cancer surgery compared with TIVA using propofol ( 17 ). Another study ( 18 ) showed that there was no difference in overall survival (OS) or recurrence-free survival (RFS) between the two anaesthesia methods for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The stress response and immunosuppression caused by the operation stimulated the progression of tumor cells during the perioperative period. Propofol was reported to have less immunosuppression and has a lower inflammatory response than volatile drugs during the perioperative period (Lee et al, 2022). This may reduce opioid use for pain relief and may have favorable to contribute outcomes (Moorthy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The intervention groups in four studies included a comparison between RA and GA versus RA, and the two studies compared inhalational versus TIVA. [ 9 10 11 12 13 14 ] Due to overall heterogeneity and lack of data in the studies, two studies were used for data synthesis for the primary outcome of cancer recurrence. Gottschalk et al .…”
Section: Methodsmentioning
confidence: 99%